A collaborative multi-hop routing algorithm for maximum achievable rate. (November 2015) - Jiang, Dingde; Xu, Zhengzheng; Wang, Wenqin; Wang, Yuanting; Han, Yang
Abstract: This paper studies collaborative multi-hop communication technology in next generation wireless communications. We propose a collaborative multi-hop routing algorithm combined with clustering to improve network performance. To build the multi-hop routing with maximum achievable rate, a relation matrix is exploited to describe the possible coverage of network nodes. A clustering-based path strategy is presented to create the effective next-hop link. A collaboration strategy is proposed to construct collaborative matrix. And then by clustering and collaboration, a multi-hop routing with maximum achievable rate is successfully built. The effectiveness and the feasibility of the proposed methods are verified by simulation results.